Specification of systems with parameterised events: An institution-independent approach - Hennicker, Rolf; Knapp, Alexander (Journal of logical and algebraic methods in programming, 2022)
Event-based systems operate in an environment that signals events upon which the system reacts. Besides the control flow of such systems also their data flow is of major importance. We present an event/data-based institution which is generic in the underlying data state institution. The logic is based on previous developments [14,8] and is now extended to take into account event parameters, quantification over data, and non-deterministic choice of arguments in an institution-independent way. We show that the resulting framework forms again an institution.